MANAJEMEN PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (STUDI MULTIKASUS DI BP2IP BAROMBONG, PIP MAKASSAR DAN BP2IP TANGGERANG) (Jurnal 7 Samudra, 2016)
This research aim to describe the implementation of education and training in BP21P Harombong, PIP Makassar and BP2IP Tangerang, The present study employs qualitative approach with case study. Data collective done by (1) interview in the informant (2) Documentation study such ss photos and files. (3) observation role by being directly involved with the subjects being researched. Result of the sntdy point out that: (1) the education and training divided into three majors such as as deck, engine and port governance. (2) the estabilishment of management function has been running based on the strategic plan.(3) motivation improvement and quality assurance is currently needed in the education and training progress so that the institution will be able to deliver the professional seafarer learners with high competitiveness and meet the national andi international standart of competency.